2013
DOI: 10.1088/1367-2630/15/4/043047
|View full text |Cite
|
Sign up to set email alerts
|

Coulomb stable structures of charged dust particles in a dynamical trap at atmospheric pressure in air

Abstract: A mathematical simulation of a dust particle's behavior in the electrodynamic linear quadrupole trap with closing end electrodes allowed us to reveal several features of the phenomena. Regions of stable confinement of a single particle, in dependence of frequency and charge-to-mass ratio, were determined. With an increase of the medium's dynamical viscosity, the region for confining charged particles by the trap becomes wider. We obtained values of the maximum quantities of charged particles confined by the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 17 publications
0
33
0
3
Order By: Relevance
“…Расстояние между сечения-ми, в которых располагались коронирующие и заземленные электроды, составляло 13 мм. Заряд частиц определялся с помощью линейной электродинамической ловушки [9]. Подробное описание используемого метода измерения заряда дано в работе [10].…”
Section: методы получения заряда на частицах микронного размераunclassified
“…Расстояние между сечения-ми, в которых располагались коронирующие и заземленные электроды, составляло 13 мм. Заряд частиц определялся с помощью линейной электродинамической ловушки [9]. Подробное описание используемого метода измерения заряда дано в работе [10].…”
Section: методы получения заряда на частицах микронного размераunclassified
“…The images in Figure 7 were obtained in a "4-bar" MQIT consisting of four identical conducting bars, collinear in the z direction and arranged on the corners of a square in the xy plane [19]. The bars had a diameter of 3.2 mm, and their nearest separation was 6.7 mm.…”
Section: D Damped Ion Trapsmentioning
confidence: 99%
“…Moreover, MQITs are quite inexpensive to construct, levitating particles in air using 50-60 Hz electric fields, making them well suited for teaching [17,18,10]. Besides individual particles, MQITs can also trap large numbers of charged particles that self-organize into Coulomb crystalline structures [18,10,19].…”
Section: Introductionmentioning
confidence: 99%
“…Linear electrodynamic quadrupole traps were used to create and study stable extended Coulomb structures containing thousands of charged dust particles . Studies have shown that linear traps are able to confine charged dust particles in air flows, and they can be used as selective filters for the purification of air from the dust particles .…”
Section: Introductionmentioning
confidence: 99%